2015
DOI: 10.1136/bmjopen-2014-007413
|View full text |Cite
|
Sign up to set email alerts
|

Who is in control? Clinicians’ view on their role in self-management approaches: a qualitative metasynthesis

Abstract: ObjectiveTo explore clinician perceptions of involvement in delivery of self-management approaches.SettingAll healthcare settings.DesignEBSCO, Scopus and AMED databases were searched, in July 2013, for peer-reviewed studies in English reporting original qualitative data concerning perceptions of clinicians regarding their involvement in or integration of a self-management approach. Of 1930 studies identified, 1889 did not meet the inclusion criteria. Full text of 41 studies were reviewed by two independent rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
84
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(90 citation statements)
references
References 42 publications
5
84
0
1
Order By: Relevance
“…Emerging research has shown that healthcare professionals can have very different understandings of self-management support (Mudge, Kayes, & McPherson, 2016;van Hooft, Dwarswaard, Jedeloo, Bal, & van Staa, 2015;Young et al, 2015). This supports our view and that of others that it is imperative to train whole teams, preferably using methods to facilitate interprofessional discussion and exchange (Reeves, Perrier, Goldman, Freeth, & Zwarenstein, 2013).…”
Section: How Is Self-management Support Actually Integrated In Practice?supporting
confidence: 72%
“…Emerging research has shown that healthcare professionals can have very different understandings of self-management support (Mudge, Kayes, & McPherson, 2016;van Hooft, Dwarswaard, Jedeloo, Bal, & van Staa, 2015;Young et al, 2015). This supports our view and that of others that it is imperative to train whole teams, preferably using methods to facilitate interprofessional discussion and exchange (Reeves, Perrier, Goldman, Freeth, & Zwarenstein, 2013).…”
Section: How Is Self-management Support Actually Integrated In Practice?supporting
confidence: 72%
“…As some authors have noted if decision-making is made primarily by healthcare professionals, this can restrict individuals from developing personal control and autonomy. [7][8][9][10] While most rehabilitation purports to be patient centred, the level of collaboration in processes such as goal setting can be inconsistent. 10 In addition, selfmanagement support interventions designed specifically for patients with stroke are relatively rare.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Part of this tension may be associated with the complexity of balancing protective aspects of care (e.g. ensuring patients avoid harmful consequences) with elements of patient choice and responsibility (22). This links to the clinicians' tendency towards self-blame, assuming responsibility when their diabetes patients do not achieve targets (23).…”
Section: Why Is Dsme Not Considered An Important Branch Of Diabetology?mentioning
confidence: 99%